Factors affecting the desertion of students of the first cycle of distance education in the school of administration, «University Señor de Sipán». Periods 2011-i to 2013-i: guidelines for reduce the desertion - Ruiz Palacios, Miguel Angel (2018)
This paper investigates the factors that influence in the drop-out of university students, of the first cycle of distance education belonging to the administration school of the university Lord of Sipán, between 2011-I to 2013-I. It addresses the individual, socio-economic, academic and finally institutional factors.Among the individual factors, the one that most influenced the drop-out was the lack of time dedicated to the study (53% of the total respondents). With regard to socio-economic factors such as: employment status, salaries received, dependents, etc. none of them influenced student dropouts (79.3% of all respondents). Among institutional factors such as: care received, administrative support, virtual environment, etc. did not influence desertion. Finally, academic factors such as: conformity with curriculum, training received, etc., were not relevant in desertion.